Future Directions in HDL Research - Helwick, Caroline (MD Conference Express, 2007)
Over the past decades, guidelines have evolved toward a much more aggressive approach to lowering lipids. Despite this, large numbers of cardiovascular events continue to occur. This clearly demonstrates that lowering low density lipoprotein is not sufficient, and that additional interventions are needed. Developing therapies which raise high-density lipoprotein (HDL) have become promising targets. Many researchers believe that HDL interacts with the vascular wall to promote removal of cholesterol.